(untitled) (Quest Journal of Management and Social Sciences, 2022)
Background: Quality health services, education and training, play a pivotal role in expanding the productivity and income of the people. The government’s expenditure on education, health and social sector is increasing rapidly in developing countries like Nepal. The increasing public spending has helped achieve the MDGs targets and is helping to meet the SDGs targets. Objectives: This study is engrossed in measuring the impact of the government’s expenditure on education, health and social sector on the economic growth of Nepal. Methods: The fundamental Cobb-Douglas production function is applied to measure the economic growth of the Nepalese economy. The unit root and stationarity of variables are checked through ADF, PP and KPSS. The time series econometric model of ARDL is used to explore the short-run and long-run relationship of the variables. The validity of the ARDL model is also examined to verify the authenticity of the econometric outcome. Results: The study has anticipated that the government’s education expenditure is inversely related to real GDP. In contrast, the health expenditure has shown a negative impact in the same year but a positive one in the lagged year. Similarly, the government’s social expenditure and gross capital formation have a negative effect on the same year, whereas they exhibited a significant positive impact in the lagged year. Further, In the long run, the government’s education and health expenditures negatively impact (-0.7233 and -0.0055), respectively in, growth. Similarly, the government’s social sector expenditure (0.20189) and gross capital formation (0.14610) positively impact Nepal’s economic growth. Conclusion: The econometric results of this study explain that the government’s expenditure on the education and health sector has a negative impact on economic growth, and the social sector and gross capital formation have a positive impact on the economic development of Nepal. The investment in such sectors by the public sector of the private sector is significant to increase the labour force’s productivity and enhance the livelihood of the poor people. Further, it reveals that the human capital investment is a continuous process and takes a generation or more to expose the outcome in the real sense.